Existence of Multiple High-Energy Solutions for a Kind of Superlinear Second-Order Elliptic Equations - Fangfang Huang; Qiongfen Zhang (Journal of Mathematics)
In this paper, we intend to consider infinitely many high energy solutions for a kind of superlinear Klein–Gordon–Maxwell systems. Under some suitable assumptions on the potential function and nonlinearity, by using variational methods and the method of Nehari manifold, we obtain the existence result of infinitely many high energy solutions for this kind of systems, which improves many relative results in the literature.